VARK: Kajian Survei dalam Domain Kognitif Keilmuan dari Mahasiswa Sebuah Universitas Terbesar di Kota Surakarta - Sulistyanto, Hernawan (Prosiding University Research Colloquium, 2021)
This research is a quantitative study that examines the preferences of Visual, Auditory, Read/Write, Kinesthetic (VARK) learning styles in the scientific cognitive domain. Three groups of students with different scientific backgrounds were compared to obtain the latest facts about differences in learning style preferences. Data was collected online based on the VARK questionnaire version 7.1 of 270 students in three different study programs from a public university in Surakarta City, Indonesia. The results show that the differences in knowledge being studied by students in different study programs make a significant contribution to the differences in learning style preferences of each student. However, the difference is not much difference between students in the same study program, both male and female. This difference in learning style preferences provides a sign for educators to design innovative learning process models that are tailored to students' learning style preferences.